Evaluation of the biosafety of recombinant lactic acid bacteria designed to prevent and treat colitis - de Moreno, Maria Alejandra (2016)
Inflammatory bowel diseases (IBDs) affect the gastrointestinal tract and are characterized by recurrent inflammation that requires lifelong therapies. Probiotics such as lactic acid bacteria (LAB) have been proposed to complement current treatment protocols for these patients; however, their characteristics are strain dependent. In this regard, certain novel characteristics are only possible through the genetic modification of these beneficial micro-organisms. Different delivery systems, such as protein delivery of anti-oxidant enzymes and anti-inflammatory cytokines, have been shown to be effective in preventing and treating IBD in animal models. In this study, the safety of the recombinant LAB (recLAB) Streptococcus thermophilus CRL807: CAT, S. thermophilus CRL807: SOD, Lactococcus lactis NCDO2118 pXILCYT: IL-10, L. lactis MG1363 pValac: IL-10 and L. lactis MG1363 pGroESL: IL-10 with proven beneficial effects was compared to their progenitor strains S. thermophilus CRL807, L. lactis NCDO2118 or L. lactis MG1363. The prolonged administration of these genetically modified strains showed that they were just as safe as the native strains from which they derive, as demonstrated by normal animal growth and relative organ weights, absence of microbial translocation from the gastrointestinal tract, normal blood parameters and intestinal histology. The results show the potential use of these recLAB in future therapeutic formulations; however, the use of modern bio-containment systems is required for the future acceptance of these recLAB by the medical community and patients with IBD.